A HUGE RIGHT STAGHORN RENAL STONE : A CASE REPORT - Khotimah, Khusnul; maulana, Akhada; Evianto, Evan; Widiyanto; Fatrahady, Lalu Shaktisila; Putrawan, Sanditias (Lombok Health And Science Journal, 2022)
Introduction: Urolithiasis is a very common problem. Open stone surgery is used less commonly due to its invasiveness and availability of above mentioned techniques. We introduce a case, that due to heavy and complex stone burden and increased chance of failure of percutaneous nephrolithotomy, Open stone surgery is performed and preferred for stone removal. Case presentation: The patient is a 58-years-old, male, had previously examined at the Dompu Hospital and referred to Urology Departement in RSUDP NTB due to a large right Staghorn kidney. After full evaluation and due to extensive spread of stone horns to the even peripheral calyces, open stone surgery performed successfully, that postoperative dynamic renal studies revealed, and evaluate kidney function. Conclusion: In spite of wonderful advances in endourologic stone surgery, open stone surgery still has its role, but it must be done in experienced centers with good surgical expertise to retain good and make acceptable functional kidney, postoperatively